2020
DOI: 10.1007/s13346-020-00833-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel rhein–phospholipid complex targeting skin diseases: development, in vitro, ex vivo, and in vivo studies

Abstract: Rhein (RH), an anthraquinone derivative, has proven to be a promising molecule for treating several skin disorders thanks to its pleiotropic pharmacological activities like antimicrobial, antifungal, antioxidant, and anticancer. However, RH's low water and oil solubility and poor skin permeability halted its topical delivery. This is the first work to investigate the expediency of tailoring a rhein-phospholipid complex (RH-PLC) to improve RH challenging physicochemical and skin permeability properties. The pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…For example, Li et al found that HPDM-rhein can cross the blood-pancreatic barrier and specifically aggregate in the lungs, thereby improving acute lung damage caused by pancreatitis (AP) [ 109 ]. And rhein-phospholipid complex (RH-PLC) improves the solubility and skin permeability of rhein [ 110 ]. Multiple substitutions at other sites can enhance pharmacological activity, such as enhancing antitumor activity [ 111 , 112 ] and antibacterial [ 113 ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For example, Li et al found that HPDM-rhein can cross the blood-pancreatic barrier and specifically aggregate in the lungs, thereby improving acute lung damage caused by pancreatitis (AP) [ 109 ]. And rhein-phospholipid complex (RH-PLC) improves the solubility and skin permeability of rhein [ 110 ]. Multiple substitutions at other sites can enhance pharmacological activity, such as enhancing antitumor activity [ 111 , 112 ] and antibacterial [ 113 ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…CHS-CA-NRs morphology was assessed compared to non-functionalized CA-NRs using TEM (JEM-100S, JOEL Ltd, Japan) after uranyl acetate staining on a carbon- laminated copper grid (Ebada et al. 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The inherent fluorescence attributes of CA (Ebada et al. 2021 , 2021 ) was exploited to determine the residence time and to assess the cartilage-targeting ability of different intra-articular CA-NRs. Fluorescence was quantified in cartilage sections at different intervals in healthy or arthritic knee joints following previous report with some modifications (Sacchetti et al.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, due to its amorphous nature, PL diffractogram showed a single broad peak at 20°. 47 Whereas the diffraction pattern of the physical mixture retained both the characteristic crystalline peaks of Fas and the broad peaks of PL, the crystalline peaks disappeared in the case of Fas/ PL complex indicating a change in the physicochemical properties of Fas suggesting successful complex formation with PL.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 96%
“…Phospholipid spectrum exhibited a band between 2925 and 2854 cm −1 corresponding to CH 2 , a band at 1736 cm −1 due to C=O stretching, P-O asymmetric and symmetric vibration bands at 1243 cm −1 and 1090 cm −1 , respectively, and a band at 969 cm −1 corresponding to N + (CH 3 ) 3 stretching. 47 Fas/Pl physical mixture showed comparative spectral analysis with no shift in the absorption peaks of either the drug or the phospholipid. On the other hand, the proposed complex FTIR chart showed significant changes in many peaks.…”
Section: Physicochemical Characterization Of Fas/ Plmentioning
confidence: 99%